IMPLEMENTASI PERATURAN BUPATI NOMOR 70 TAHUN 2022 TENTANG ALIH MEDIA ARSIP DI DINAS ARSIP DAN PERPUSTAKAAN KABUPATEN SUMEDANG - Yadi, Agus Fitri (JRPA - Journal of Regional Public Administration, 2025)
Media transfer is the transfer of documents from physical form (hard files) to digital form (soft files) so that they can be managed with information technology. Archives stored in digital format are called electronic archives. To ensure its authenticity, authentication is carried out, namely giving a sign or written statement that the archive is original or according to the original. This research aims to find out how the implementation of Regent Regulation Number 70 of 2022 concerning Archive Media Transfer at the Sumedang Regency Archives and Library Office. The method used is qualitative, with informants consisting of the Head of the Office, the Head of the Archives Division, and two functional staff archivists. Data collection techniques include literature study and field study (observation, interviews, and documentation). The data analysis process includes data reduction, data presentation, verification, and triangulation.The results showed that the policy implementation has been running quite well with the support of communication, resources, disposition, and bureaucratic structure. However, there are obstacles in the form of limited facilities, competency gaps due to employee rotation, and suboptimal coordination between fields. Improvement efforts are made through training, resource utilisation, and credit-based evaluation. It is recommended that there be an increase in facilities, training before rotation, acceleration of SOPs, and periodic socialisation.